Contested Sustainability The Political Ecology of Conservation and Development in Tanzania - Ponte, Stefano; Noe, Christine; Brockington, Dan (Eastern Africa Series, 2022)
Richly detailed and timely study on conservation, development and sustainability in Tanzania. Provides valuable insights into the successes and failures of the management and governance of wildlife, forestry and coastal resources. Responding to the urgent need to examine the outcome of interventions in governing natural resources, this book analyses different types of sustainability partnerships - with donors, governments, business, NGOs and other actors, and, crucially, assesses which result in better livelihood and environmental outcomes. The contributors, from a range of disciplines, compare 'more complex' partnerships to relatively 'simpler', more traditional top-down and centralized management systems and to location where sustainability partnerships are not in place. Within-sector comparisons allow a fine-tuned analysis that is formed of historical, location and resource-specific issues, which can be used as input for resource-specific policy and partnership design. Experiences and lessons can be drawn from comparisons across the three different sectors, which can be applied to natural resource governance more broadly. This book is openly available in digital formats under Creative Commons license CC BY-NC-ND.